Ethnographic studies in international human resource management: Types and usefulness. (May 2020) - Mahadevan, Jasmin
This article provides a first conceptual discussion of the usefulness of ethnography for International Human Resource Management. In line with its original anthropological meaning, ethnography is understood as a multi-paradigmatic mindset involving five interrelated strands, all of which have the potential to contribute to International Human Resource Management studies. Structural-functionalist ethnography enables deep comparison and can thus contribute, for instance, to meeting the structural and institutional integration challenges of International Human Resource Management. Interpretive ethnography sheds light onto the hidden realities of International Human Resource Management and can thus help, for example, to acknowledge the diversity of employee and stakeholder experiences. Critical, postmodern, and postcolonial ethnography reveal the power-inequalities associated with diverse frameworks, practices, and work experiences in a global context. They can thus help overcome the inherent power-inequalities of International Human Resource Management and might utilize previously marginalized knowledge for the development of alternative International Human Resource Management strategies and practices. Yet, leveraging the full potential of ethnography for International Human Resource Management studies requires International Human Resource Management scholars not to borrow pre-selected ethnographic approaches, such as interpretive ethnography, from related disciplines, such as International Business and Cross-Cultural Management, because these might not fit the specific needs of International Human Resource Management. For facilitating this goal, this article provides a first multi-paradigmatic discussion of the development and principles of ethnography in anthropology, and its present and potential contributions to International Human Resource Management studies. It is not a guide of how to do ethnography, but a roadmap enabling future International Human Resource Management researchers to choose their ethnographic research strategy consciously, reflexively, and as their research interest demands for.